Трансформація життєпридатності в небезпеку - головний тренд еволюції міського середовища України 21 століття. Теоретико-методологічний аналіз - Трофимчук, О.М.; Калюх, Т.Ю.; Калюх, Ю.I. (Екологічна безпека та природокористування, 2009)
In article are considered system risks, characteristic for the big cities, on an example of Kiev and Krivoi Rog. The expediency of working out of the scientific concept accoding to system risk of residing in cities of Ukraine and scientific researches in sphere of safety and a sustainable development of the Ukrainian cities is proved.